Skin prick test reactivity in atopic children and their number of siblings - Beatrix Siregar; Lily Irsa; Supriatmo Supriatmo; Sjabaroeddin Loebis; Rita Evalina (Paediatrica Indonesiana, 2015)
Background Some studies have shown that low birth order is a risk factor for developing atopy, although these results remain inconclusive. Those studies put forth the hygiene hypothesis, which states that early childhood infections in siblings may protect against atopy. Hence, an inverse relationship between family numbers and atopy was found. Atopy may be diagnosed from a history of atopy in an individual or his family, and can be confirmed by specific IgE for allergens or positive skin prick tests.Objective To assess for an association between skin prick test reactivity in atopic children and their number of siblings.Methods A cross-sectional study was conducted in May to June 2010 in elementary school children at the Kampung Baru District, Medan Regency, North Sumatera. Subjects were divided into two groups. Group I had children with < 3 siblings and group II had children with â‰¥ 3 siblings. Skin prick tests were done in 7 to 10-year-old children with a history of asthma, allergic rhinitis and atopic dermatitis. Skin prick test reactivity results were analyzed by Chi-square test.Results A total of 192 subjects were enrolled in this study, with 96 subjects in each group. Positive skin prick tests were significantly higher in subjects with <3 siblings than in those with >3 siblings (75% and 53.1%, respectively; P=0.003).Conclusion Atopic children with <3 siblings had more positive skin prick tests than children with >3 siblings.